The Hierarchy of Defense Mechanisms: Assessing Defensive Functioning With the Defense Mechanisms Rating Scales Q-Sort - Di Giuseppe, Mariagrazia; Perry, J. Christopher (Frontiers in Psychology, 2021)
The psychodynamic concept of defense mechanisms is nowadays considered by professionals with various theoretical orientations of great importance in the understanding of human development and psychological functioning. More than half century of empirical research has demonstrated the impact of defensive functioning in psychological well-being, personality organization and treatment process-outcome. Despite the availability of a large number of measures for their evaluation, only few instruments are based on the gold-standard theory for the assessment of the whole hierarchy of defense mechanisms, known as the Defense Mechanisms Rating Scales (DMRS). The present article illustrates the theoretical and methodological background of the DMRS-Q, the Q-sort version of the DMRS for clinical use. Starting from the definition and function of the 30 defense mechanisms included in the hierarchy, we extracted 150 items that better captured a full range of defensive manifestations according to the DMRS theory. The DMRS-Q set is described in this paper with reference to the DMRS manual. Directions for using the DMRS-Q online software for the free and unlimited coding of defense mechanisms are also provided. After each coding, the DMRS-Q software provides a report including qualitative and quantitative scores reflecting the individual’s defensive functioning. Qualitative scores are displayed as the Defensive Profile Narratives (DPN), while quantitative scores are reported as Overall Defensive Functioning (ODF), defensive categories, defense levels, and individual defense mechanisms. Syntax for the scoring is displayed in the results and exemplified in a clinical vignette of a psychotherapy session coded with the DMRS-Q. The DMRS-Q is an easy-to-use, free, computerized measure that can help clinicians in monitoring changes in defense mechanisms, addressing therapeutic intervention, fostering symptoms decreasing and therapeutic alliance. Moreover, the DMRS-Q might be a valid tool for teaching the hierarchy of defense mechanisms and increase the observer-rated assessment of this construct in several research fields.